(untitled) (Journal of Hama University, 2019)
The switched reluctance motor is suitable for many electric traction applications due to it’s simple low-cost structure, making it an economical solution for high and variable speeds. Nowadays, the interesting of this type of motor has increased thanks to emergence of real-time programmable circuits, including FPGAs.In this article, we present a control algorithm for driving switched reluctance motor including the switch algorithm and the electronic switch function. For this reason, we build an analytical model of the motor which takes account the magnetic behavior of the motor and Suppose that the Mutual inductance between the phases is neglected, but the resistance of the phase file has been taken account.The driving of this motor requires precise position of the rotor at each moment of operation, so a position sensor was used to obtain the position angle to obtain three currents reference. These signals are compared with the actual signals from the current sensors, Based on, the driving pulses are applied to the bases of transistors. Current regulation, and therefore torque, is the basis of driving systems of this type of motor, in order to obtain the required response to both torque and speed. For this reason, the current control technique was used for control algorithm which permits to obtaining the required current for a wide range of speed. The inherited ripples of the motor torque is a main problem, so the hysteresis current control is proposed in this paper which doesn’t allow the current to vary within a wide range, that results in high reliability in the modern drive systems where the ripples are minimum and the acoustic noise is reduced .